Numerical abnormalities of permanent dentition - a case report - Decusara, Mioara; Cornea, Daniela; Rusu-Negraia, Magdalena; Șincar, Cerasella Dorina (Medicine and Pharmacy Reports, 2021)
Tooth number abnormalities may occur under the influence of genetic or environmental factors which intervene in the tooth formation stages (induction and proliferation), most commonly the permanent dentition being affected. The result is the appearance of dental anomalies with numerical deficiency (hypodontia, anodontia), or with dental excess (hyperodontia, over-teeth). In this paper we report a case of a 15-year-old boy with associated abnormalities of permanent dentition: mesiodens and palatal impacted cuspid at the maxillary dental arch and incisor anodontia at the mandibular dental arch. Orthodontic treatment aimed at resolving maxillary dental crowding, obtaining dental alignment, a stable and functional occlusal relationship and a satisfactory smile for the patient.